2018
DOI: 10.1021/acsnano.7b07432
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Correlations in Random Ionomers

Abstract: Understanding the electrostatic interactions in ion-containing polymers is crucial to better design shape memory polymers and ion-conducting membranes for multiple energy storage and conversion applications. In molten polymers, the dielectric permittivity is low, generating strong ionic correlations that lead to clustering of the charges. Here, we investigate the influence of electrostatic interactions on the nanostructure of randomly charged polymers (ionomers) using coarse-grained molecular dynamics simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 56 publications
(91 reference statements)
2
73
0
Order By: Relevance
“…The charge not only changes interfacial adsorption of these copolymers but can also modulate the self-assembled morphologies in bulk chloroform due to electrostatic correlation driven aggregation. 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The charge not only changes interfacial adsorption of these copolymers but can also modulate the self-assembled morphologies in bulk chloroform due to electrostatic correlation driven aggregation. 18…”
Section: Discussionmentioning
confidence: 99%
“…16 In organic media, on the other hand, ionic correlations in charge-containing copolymers lead to the formation of ionic clusters. 1822 The ionic clusters can lead to nontrivial thermodynamic changes in the molten state, such as the evolution of inverted phases, 6,23 and ion-dependent miscibility of ion-conducting block copolymers. 24 Theoretical developments have identified the effects of ion–ion correlations, 2529 solvation energy of ions, 3033 and translational entropy of ions as significant influences on determining the thermodynamics of charge-containing copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…For matrix-free model systems [34,35] it was observed that NPs diffuse similarly to a polymer solution [36][37][38], while chains diffuse faster than NPs [39]. Ionic interactions are also included in the case of ionomers in which the morphology and phase behavior depend on the electrostatic strength [40][41][42]. In particular, ionic clusters are formed by increasing the electrostatic strength developed from linear to branched structures [40].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic interactions are also included in the case of ionomers in which the morphology and phase behavior depend on the electrostatic strength [40][41][42]. In particular, ionic clusters are formed by increasing the electrostatic strength developed from linear to branched structures [40]. In a simulation of ionomer (poly(ethylene-co-methacrylic acid)) nanocomposites [43], it was observed that ions were depleted around a neutral NP, but they were denser relative to the bulk value in the case of a sticky NP.…”
Section: Introductionmentioning
confidence: 99%
“…17 mV dec À 1 lower than that of Cu plate, implying the improved OER rate on a Cu/PVdF-HFP fibrous catalyst. The obtained Tafel slope value is little larger than the layered transition metal catalyst (e. g. 40 mV dec À 1 for NiFe-LDH in 1 M KOH [52] ), comparable with the transition metal oxide catalyst (e. g. 60 mV dec À 1 for Mn 3 O 4 in 1 M KOH [53] ) as well as the precious metal oxide catalysts (e. g. 55 mV dec À 1 for RuO 2 and 91 mV dec À 1 for IrO 2 in 0.5 M KOH [54] ), and smaller than the most of the perovskite-based catalysts (70 mV dec À 1 for LaCoO 3 and 91 mV dec À 1 for La 0.8 Sr 0.2 O 3 in 1 M KOH [20] ). It is unlikely that the unique fibrous structure of Cu/PVdF-HFP fiber catalyst affects the energetics of the OER; the much higher specific OER activity of Cu/PVdF-HFP fiber compared to the Cu plate is probably due to the synergetic effect between Cu and PVdF-HFP.…”
Section: Oxygen Evolution Reaction Activitymentioning
confidence: 70%